Assessing the Narratives of the Role of Higher Education in Northern Ghana: The Case of University for Development Studies - Intsiful, Emmanuel (African Journal of Education and Practice, 2017)
Purpose: The main purpose of this study was to examine the role of University of Development Studies (UDS) in enhancing socio-economic development in northern Ghana, and secondly, to ascertain whether or not knowledge production and the universities are part of national development strategy. Methodology: In aiming to achieve the descriptive and exploratory objective of the study, the research design adopted for this study was a Case study. The study employed a qualitative approach as its research strategy. A semi-structured interview guide and document analysis was used to answer the research questions. A critical data analysis was done based on open-coding, axial coding, and selective coding. Results: The study revealed that the "˜university as an instrument' and "˜university as an ancillary' were the dominant notion emphasized as the key role of UDS, which in essence translate into minimal or somewhat absence of use of Knowledge production and the university in national development strategy. Policy Recommendation: It is recommended that a policy framework should be agreed by key stakeholders that will link the university activities to national development plan which will not only stimulate socio-economic development but to contribute towards the global knowledge economy since global happenings has permeated both national and local levels.